Rethinking South Asia : scenarios for a changing geopolitical landscape - Wagner, Christian (2017)
Zusammenfassung: A number of developments suggest that South Asia’s political geography will be restructured in the medium to long term. The main external drivers are infrastructure projects - first and foremost the Chinese Belt and Road Initiative (BRI) - which open up new development opportunities for many countries in the region. At the same time relations between India and Pakistan, which were are the heart of any analysis on South Asia, are becoming increasingly decoupled. The already weak South Asian Association for Regional Cooperation (SAARC) may become even less important and is likely to be replaced by new cooperation formats